Isolation and Characterization of Amylolytic Bacteria From Peatlands Area in Central Kalimantan - Nafisah, Zahrotun; Elya Resha, Enjel; Oksal, Efriyana; Ayu Pratika, Remi; Hermayantiningsih, Dwi; Riana Dewi, Syahrani; Ayu Andhita, Naswa (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2025)
Peatlands in Central Kalimantan, Indonesia, are ecologically significant due to their acidic, organic-rich conditions, yet their microbial communities remain underexplored, particularly regarding their enzymatic potential. This study aimed to isolate and characterize amylolytic bacteria from peat soil collected at a depth of 143–150 cm in the LAHG CIMTROP area of Central Kalimantan. A total of 44 bacterial isolates were obtained using serial dilution and the gridding method. Screening for amylase activity identified isolate ENS31 as having the highest activity, shown by a clear halo on starch agar. ENS31 was further subjected to biochemical characterization and enzyme activity assays. The amylase enzyme exhibited optimal activity at pH 7 and 50°C, with a specific activity of 3.5 U/mg, and retained activity up to pH 12 (2 U/mg). These results indicate that ENS31 produces an enzyme stable in alkaline conditions despite originating from an acidic environment, demonstrating potential for industrial applications requiring pH and temperature-tolerant biocatalysts. This study contributes to understanding the functional diversity of peatland microbes and highlights tropical peat ecosystems as promising sources of novel enzymes.